Enhancing Legal Certainty for Consumers in Apartment Unit Trade: A Comparative Analysis of Dispute Settlement Agreements in Indonesia and the Netherlands - Yuniyanti, Salma Suroyya; Siska, Frency; Dian, Azni binti Mohd (Universitas Negeri Semarang, 2024)
The purpose of this study is to analyze the dispute settlement binding Trade Agreement (PPJB) unit flats through litigation in Indonesia compared to the Netherlands and to analyze the reconstruction of the law in dispute resolution PPJB in Indonesia to provide legal certainty. The main problem in this paper is that the dispute resolution of the binding Trade Agreement in Indonesia has not provided legal certainty due to court decisions that are difficult to implement due to weak supervision. This research method is normative research with a comparative approach. The urgency of this study is that 276 PPJB disputes in Indonesia are resolved through the courts are difficult to implement. The novelty of this study lies in the researchers ' efforts to reconstruct the law of flats, especially in the implementation of PPJB dispute court decisions. The results showed PPJB dispute settlement unit flats through litigation, experienced obstacles in the application of the judge's ruling, which won the consumer as the injured party. The obstacles to the application of the ruling do not provide legal certainty for consumers. In the Netherlands, the settlement of flat sale and purchase disputes is carried out through non-litigation channels that are more effective in providing legal certainty. Legal reconstruction in PPJB dispute resolution in Indonesia to provide legal certainty that is to accommodate the provisions of supervision for putting the court's decision into action or arbitration decisions in PPJB dispute resolution, as outlined in the provisions of Article 105 of the flats law.